Arctic National Wildlife Refuge : hearing before the Committee on Energy and Natural Resources, United States Senate, One Hundred Fourth Congress, first session . August 2, 1995. - United States. Congress. Senate. Committee on Energy and Natural Resources. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1996)
Shipping list no.: 96-0148-P. Distributed to some depository libraries in microfiche. Includes bibliographical references. Mode of access: Internet.